Contemporary Museums : Architecture, History, Collections - Chris Van Uffelen
Museums are some of the great architectural hallmarks of any place. Since the discovery of the ,,Bilbao Effect", triggered at the end of the last century by the Frank O. Gehry's building, new museums have been emerging all over the world. The volume presents the most varied forms of exhibition buildings of the last decade and reveals their varied spatial and architectural concepts: from the white cube idea that exists chiefly to display the exhibit itself, to a flamboyant freestanding structure, which enriches the image of the city and involves the works in its dynamic spatial configuration. A broad diversity of museums is considered: museums of businesses and institutes, of technology and toys, of literature and architecture. It is the art museums, however, which represent the principle focus: from collections of the old masters, handed down through generations, to small, private collections of contemporary art. The texts focus on the architecture and design of each museum as well as the collection housed within it